Case Report: Multimodality imaging of a bronchogenic cyst in the interatrial septum - Mingming, Ma; Yana, Zhao; Ran, Chen; Qingqing, Zhu; Bowen, Zhao (Frontiers in Cardiovascular Medicine, 2024)
Intracardiac bronchogenic cysts (IBCs) are very rare. To date, only a few cases of IBC have been reported in the literature. We report a case of a bronchogenic cyst that arose from the interatrial septum in a 42-year-old man who presented with symptoms of palpitation. A unilocular cystic lesion of the heart was found initially on echocardiography and subsequently on computed tomography and magnetic resonance imaging. The diagnosis was further confirmed by histopathology after surgical resection. Multimodality imaging played a crucial role in the diagnosis and treatment of such rare lesions.